Development of Compensation in the Standards of International Assessment Programs for Future Teachers - Gullola O'rmonbekova Yuldashboy qizi (Zien Journals, 2022)
In this article, it is mentioned about the development of potential teachers ' compensation in the standards of international assessment programs. Also, the author presents proposals and recommendations on the development of the corporate system, stages and pedagogical model of the development of socio-cultural competence in future teachers
Keywords: future teacher; competence; competencequalification requiremens model